Genome-Wide Profiling of Human Papillomavirus DNA Integration into Human Genome and Its Influence on PD-L1 Expression in Chinese Uygur Cervical Cancer Women - Feng Yang-chun; Wang Sen-yu; Zhang Yuan; Huang Yan-chun (Journal of Immunology Research)
Background. The Uygur is the fifth most populous ethnic group in China. Compared to other Chinese population, cervical cancer in them had high incidence, and HPV infection also was particular. Their HPV integration situation has never been reported. We aimed to investigate the integration situation of 20 subtypes of HPV gene into host cell genome in Chinese Uygur cervical cancer patients; meanwhile, we explored the influence of gene integration on PD-L1 expression. Methods. 40 frozen Chinese Uygur cervical cancer specimens with positive HPV infection were obtained from the cancer prevention and treatment institute of Tumor Hospital Affiliated to Xinjiang Medical University. The integration situation of HPV gene into host cell genome was detected by Agilent SureSelect™ Target Enrichment Chip and Next-Generation Sequencing. The related genes were analyzed by GO functional annotation and KEGG pathway enrichment. The expression levels of PD-L1 in cancer cells were tested by immunohistochemical assay (IHC). Meanwhile, the relationship between PD-L1 levels in cancer cells and gene integration were analyzed. Results. The HPV multiple infection rate by HIVID was as high as 92.5%, much higher than 35.0% by the commercial kit (P<0.05). There were 13423 integration events in 40 specimens, involving 6867 human genes. These integration events were distributed on all human chromosomes, and chromosome 19 had the excessive concentration phenomenon of integration events. There were some integration hotspots in human genome such as PPP1R37, HECW2, EMBP1, ANKRD50, SPTBN4, LINC00895, LYRM4-AS1, LINC00374, RBFOX1, CSMD1, CDH13, and KLHL4. Insertion breakpoints can be found in all gene regions of the HPV genome. The actual observation of the integration times of E1 and E6 was much higher than the expected value, while the actual observation times of E5 were much lower than the expected value. The result of GO functional analysis showed that binding molecular function and cellular process biological process were the main ways to influence the cell biological behavior of HPV gene integration. The enrichment pathway analysis of KEGG showed that pathways in cancer were the most important enrichment pathways involved in the genomic integration of HPV. The positive PD-L1 rate was 62.5%. Logistic regression analysis showed that 9p24.1 existing integration sites and the number of all gene integration were risk factors for PD-L1 expression (odds ratio 17.313 and 1.012; 95% confidence interval 1.691-177.213 and 1.001-1.023). Conclusions and Relevance. Most high-frequency sites of HPV integration in Chinese Uygur cervical cancer are related to cancer progression, and the gene integration hotspots may be potential HPV carcinogenic targets. The problem of multiple HPV infection in Chinese Uygur cervical cancer patients should be paid attention. L1 and E6 genes are inapposite as the target gene of commercial HPV type detection kit, because of high-frequency breakpoints in these genes. The gene integration especially the integration existing on 9p24.1 could affect the expression level of PD-L1.